Product Related Characteristics, Promotion And Marketing Mix Are Key Tools In Determining Purchase Behaviour & Purchase Decision by Teenagers - An Empirical Study - Mohanram, A. S.; Mahavi, C. (Indian Journal of Marketing, 2007)
Teenagers are influenced by updated information of the product and hence they go for information search, collect information from different dealers on various aspects like price, technology and so on. They are also influenced by peers compulsion and sales talk of the dealers. While parents apply Parents apply general response, teenagers employ two types of strategies to convince their parents. They are emotional and logical. Logical teenagers give importance to product image. Emotional teenagers try to put forth their importance by various product value attributes like utility, quality, features, durability, long term benefit and service warranty of the two-wheeler. In respect of promotion mix, various sales initiatives like store visit, stores display, multilevel marketing and sale promotion efforts like test run, free offers; finance scheme and other sales promotion techniques influencing the logical teenagers. Also advertisement in TV and print media also contribute to some extent.